Kajian pola perbandingan kepimpinan Tun Dr Mahathir sebagai Perdana Menteri di era Barisan Nasional (BN) dan Pakatan Harapan (PH) - Abdul Muthalib, Harun (2024)
Dr Mahathir Mohamad was twice appointed as Prime Minister of Malaysia, the first time in 1981 and 2018 for the second time. The post of Prime Minister he held represented two different party coalitions, namely Barisan Nasional (BN), 1981-2003 for 22 years and Pakatan Harapan (PH) in 2018 at the helm for 22 months. This study aimed to examine differences in terms of effective leadership patterns between the two eras. For the purpose of obtaining appropriate data, two methods are used, namely bibliographic studies by reference to writing materials, documents, articles, journals, articles, papers and academy books with the aim of creating conceptual images and issues that form the basis of the analysis of the study discussion. The second method through face-to-face interviews using unstructured questions involved twelve study participants comprising five politicians, five civil servants and two leaders of nongovernmental organizations. The purpose of this method is to obtain supporting data on the effective leadership practices expressed by Dr Mahathir in both eras. The summary and results of the study found that Dr Mahathir's leadership effectiveness was at a higher level in his era of leading the government under the auspices of BN than during the PH era. This is due to the encouragement and contribution of five core factors, namely the full support of BN members and leadership, the consistent absolute victory by BN in the series of elections from 1986-1999, the support of civil servants who were together in Dr Mahathir's leadership mission, the use of sanctions and containment elements on political enemies, industrialisation policies and major economic structural changes that benefited the people. The end of the study also concludes that the effective leadership of the PH era failed to be translated by Dr Mahathir due to the constraints of age, time and ideological differences and goals among PH's own component parties thus leaving Dr Mahathir without full control to determine, direct and dominate as when he was in charge of the government under the previous BN governance. The implications cause in the era of PH the country and society to suffer losses in various fields.